Comparing the closure of hepatocaval ligament using stapler or suturing in liver surgery - Batı, Imam Bakır; Tüysüz, Umut (The European Research Journal, 2023)
Objectives: Hepatocaval ligament is localized on the posterior and lateral side of the retrohepatic Inferior Vena Cava (IVC) , above the right adrenal vein. Bleeding due to retro-hepatic cava injury could sometimes occur during the dissection and closure of hepatocaval ligament (HCL). We aim to determine closing meth- ods of HCL in terms of cost, ease of application and safety. Methods: The study population included 90 recipient hepatectomy patients who had cadaveric and live-donor liver transplantation at Organ Transplant Center of Acıbadem Hospital between 2017 and 2019. The patients were divided into two groups. The first group contained 40 patients who were closed with 25 mm EndoTA 30 stapler. The second group contained 50 patients who were closed by continuous double- layer suturing with 5/0 propylene. Results: In the group closed by endovascular stapler, reinforcement suturing was performed in eight patients (20%) using 5/0 propylene suture due to mild blood leakage in the closing line. In two patients (5%), on the other hand, the staple device could not be used due to the fact that HCL was very close to the right hepatic vein and the distance between the liver and the vena cava was short. There were no perioperative and postoperative HCL-associated liver and vena cava bleeding complications in both groups. However, the cost was significantly higher in the stapler group than in the suturing group. Conclusions: The present study is the first to compare the stapler or suturing techniques for closing HCL in the receiver hepatectomy of liver transplantation. The results indicated that the closure with suturing was at least as useful and convenient in terms of cost, ease of application and safety.